Use of Titanium Elastic Nails in the Adult Diaphyseal Humerus Fractures - Upadhyay AS; Lil NA (Malaysian Orthopaedic Journal, 2017)
INTRODUCTION: Humerus shaft fractures in adults can be managed conservatively with functional braces or operatively with plate osteosynthesis or with intramedullary nailing. Conventionally humerus intramedullary nailing is done either using humerus interlocking nails or Enders nails. In this study we analyse the outcome of humerus shaft fractures (upper and middle third) managed with closed ante- grade intramedullary titanium elastic nailing in terms of union rates, union time, functional results and complications. MATERIALS AND METHODS: A retrospective analysis of 25 patients treated with ante-grade intramedullary titanium elastic nailing was done during the period of August 2014 to June 2016 at our tertiary care centre. Skeletally mature patients with closed and acute fractures of the upper and middle shaft humerus of both sexes were included in the study. RESULTS: Twenty-five (100%) fractures united with an average consolidation time of 14.98 weeks (10-32 weeks), and no fractures ended in non-union. Nail impingement was seen in two (8%), shoulder stiffness in one (4%). Functional results were excellent in 22 (88%), moderate in two (8%) and poor in one (4%). There were 17 males and eight females with an average age of 39.08 years (range: 18-65 years). The average duration of hospital stay was 3.84±2.30 days. CONCLUSION: Closed ante-grade intramedullary titanium elastic nailing offers a safe and reliable method of fixing fractures of upper humeral shaft in adults. This method provides early fracture union, high union rates and less complications, in addition to early rehabilitation and reduces the hospital stay.